2021
DOI: 10.1002/lol2.10189
|View full text |Cite
|
Sign up to set email alerts
|

Sea urchin microbiomes vary with habitat and resource availability

Abstract: Characterizing patterns in the microbial communities that dwell within key species is critical to understanding the role of microbes in shaping fundamental aspects of marine ecosystems. Sea urchins are key grazers in coastal seas, where they can survive a variety of conditions and diets, enhancing their ecological impact on kelp forests. Here we provide the first evidence that the two dominant sea urchin species in southern California have distinct gut microbiomes that vary with habitat. The taxonomic composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…Psychromonas sp. has also been detected in S. purpuratus (Hakim et al 2019;Miller et al 2021) and S. intermedius (Zhang et al 2014) and was abundant especially in gut digesta and fecal pellets, analogous to our sample material. Thus, this symbiont appears to be a common feature of the intestinal microbiome of sea urchins belonging to the Strongylocentrotus genus, which could point towards important symbiotic functions.…”
Section: Algal Food Intake Promotes a Dominant Symbiont Related To Ps...supporting
confidence: 82%
“…Psychromonas sp. has also been detected in S. purpuratus (Hakim et al 2019;Miller et al 2021) and S. intermedius (Zhang et al 2014) and was abundant especially in gut digesta and fecal pellets, analogous to our sample material. Thus, this symbiont appears to be a common feature of the intestinal microbiome of sea urchins belonging to the Strongylocentrotus genus, which could point towards important symbiotic functions.…”
Section: Algal Food Intake Promotes a Dominant Symbiont Related To Ps...supporting
confidence: 82%
“…However, future experiments are to be conducted by culturing and subsequent biochemical tests to confirm the metabolic roles of these vibrios in our samples. In a recent study, the microbiota in the gut ecosystems of red urchin Mesocentrotus franciscanus and the purple urchin Strongylocentrotus purpuratua from Southern California Kelp Forest and barrens of Southern California revealed complex habitat-specific differences [79]. The taxa distribution in these urchins and our study mainly showed insignificant common-ality.…”
Section: Discussionsupporting
confidence: 40%
“…Interestingly, the gut microbiota of red urchin Loxechinus albus from aquaculture environment [80], Antarctic heart urchins (Spatangoida) Abatus agassizii [81], green urchins Lytechinus variegatus from the U.S. Gulf of Mexico [24,25,[82][83][84], and purple urchins Strongylocentrotus purpuratus from the U.S. Oregon Coast [20] showed abundant members of the family Campylobacteraceae. In contrast, Strongylocentrotus purpuratus from Southern California Kelp Forest and barrens had insignificant abundance (<1%) of the Campylobacteraceae [79]. This observation further emphasizes the possibility that diet in the inhabiting ecosystems likely promotes specific taxonomic composition in the urchin gut environment [85].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Sea urchin has been studied for a long time as fisheries resources and model organisms of biology. However, there have been a few studies on general views of their gut microbes' structure, function, and dynamics, particularly using individuallevel metagenome approaches (Hakim et al, 2015, Yao et al, 2019Faddetta et al, 2020;Miller et al, 2021). The abundances of reads assigned to phyla Bacteroidetes and Proteobacteria were observed in the gut of Tripneustes gratilla, and those assigned to phyla Fusobacteria and Proteobacteria in Diadema setosum and Stomopneustes variolaris (Yao et al, 2019), and the order Vibrionales was abundant in wild American green sea urchin (Hakim et al, 2016).…”
Section: Introductionmentioning
confidence: 99%